2017
DOI: 10.3389/fmicb.2017.01198
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Methane Production and Oxidation in Surface Sediment from Aarhus Bay, Denmark

Abstract: Marine surface sediments, which are replete with sulfate, are typically considered to be devoid of endogenous methanogenesis. Yet, methanogenic archaea are present in those sediments, suggesting a potential for methanogenesis. We used an isotope dilution method based on sediment bag incubation and spiking with 13C-CH4 to quantify CH4 turnover rates in sediment from Aarhus Bay, Denmark. In two independent experiments, highest CH4 production and oxidation rates (>200 pmol cm-3 d-1) were found in the top 0–2 cm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 75 publications
9
50
0
Order By: Relevance
“…A similar close coupling between methane oxidation and methanogenesis in the absence of definite methane profiles was recently proposed from isotopic labeling experiments with sediments from the sulfate reduction zone of the nearby Aarhus Bay in Denmark (Xiao et al, 2017). It is therefore likely that such a cryptic methane cycling also occurs in the sulfate reduction zone of sediments in the Eckernförde Bay.…”
Section: Relevance Of Methanogenesis In the Sulfate Reduction Zone Ofsupporting
confidence: 76%
“…A similar close coupling between methane oxidation and methanogenesis in the absence of definite methane profiles was recently proposed from isotopic labeling experiments with sediments from the sulfate reduction zone of the nearby Aarhus Bay in Denmark (Xiao et al, 2017). It is therefore likely that such a cryptic methane cycling also occurs in the sulfate reduction zone of sediments in the Eckernförde Bay.…”
Section: Relevance Of Methanogenesis In the Sulfate Reduction Zone Ofsupporting
confidence: 76%
“…Although the concave‐up shape of methane profile was often interpreted as the diffusion of methane from SMTZ, increasing evidence suggested endogenous methane production could occur in the sulfate‐rich sediments (Maltby et al ; Sela‐Adler et al ; Xiao et al ; Zhuang et al ), as observed in this study. Therefore, the low but detectable concentrations of methane could be a collective result of production, consumption, and diffusion from underlying sediment below SMTZ.…”
Section: Discussionsupporting
confidence: 57%
“…The Haps cores were transferred to a PVC core‐liners (diameter 11.8 cm) on deck. The cores were then brought back to the laboratory, kept at in situ temperature (10°C) and processed within 48 h (Xiao et al ). Several Rumohr Lot cores (Meischner and Rumohr ) were taken for geochemical profiles and radiotracer microbial activity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The gross CH 4 production and oxidation rates were quantified by amending the natural pool of CH 4 with 13 CH 4 and following the subsequent replacement of the 13 CH 4 by 12 CH 4 from methanogenesis, which is referred to as bag incubation combined with 13 C isotope dilution (Xiao et al ). Briefly, two segments (0–2 cm and 8–10 cm) of sediment were sliced from Haps cores in a glove box with N 2 atmosphere and passed through a 0.5 mm sieve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation